2010
DOI: 10.3233/ch-2010-1353
|View full text |Cite
|
Sign up to set email alerts
|

Role of genetic polymorphisms in myocardial infarction at young age

Abstract: Acute myocardial infarction (AMI) in young adult presents a typical pattern of risk factors, clinical, angiographic and prognostic characteristics.In the last years we demonstrated that hemorheological profile is altered in these patients in a persistent way and independently of the number of risk factors and of the extent of coronary lesions. Thus, the hyperviscosity syndrome following AMI could be considered an intrinsic characteristic of these patients. Consequently it is possible to hypothesise the presenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 40 publications
1
31
0
2
Order By: Relevance
“…In particular, it has been demonstrated that centenarian offspring have an increased likelihood of surviving to 100 years and show a reduced prevalence of age associated diseases, such as CVD, and lower prevalence of CVD risk factors [1,30-32,50] Thus, genes involved in CVD may play an opposite role in human male longevity. Our data in male Sicilian population confirm this suggestion and emphasize the role of antagonistic pleiotropy in ageing and longevity [51,52]. A high frequency of proinflammatory CCR5wt variant, +896A TLR4 allele, -765 G Cox-2 allele, 1708A and 21 T 5-Lo alleles characterizes male Sicilian patients affected by MI (Table 3) [47-49].…”
Section: Introductionsupporting
confidence: 78%
“…In particular, it has been demonstrated that centenarian offspring have an increased likelihood of surviving to 100 years and show a reduced prevalence of age associated diseases, such as CVD, and lower prevalence of CVD risk factors [1,30-32,50] Thus, genes involved in CVD may play an opposite role in human male longevity. Our data in male Sicilian population confirm this suggestion and emphasize the role of antagonistic pleiotropy in ageing and longevity [51,52]. A high frequency of proinflammatory CCR5wt variant, +896A TLR4 allele, -765 G Cox-2 allele, 1708A and 21 T 5-Lo alleles characterizes male Sicilian patients affected by MI (Table 3) [47-49].…”
Section: Introductionsupporting
confidence: 78%
“…19 Indeed, a single nucleotide polymorphism (C1019T) within the human Cx37 gene ( GJA4 ) has been reported to be a potential prognostic marker for atherosclerosis and myocardial infarction. 48,49 Given the established role of platelet-monocyte adhesion and the initiation or progression of atherosclerosis, it is tempting to speculate that the role of platelet connexin function may extend to platelet-immune cell intercellular signalling in a range of pathological conditions.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, in an ethnically homogeneous population, different age groups showed differences in the prevalence of certain polymorphisms in interleukin genes [32]. In particular, polymorphisms in genes related to inflammation, oxidative stress [32-34] and mitochondrial DNA [35] were found to be associated with differences in longevity. Although there are some contradictory reports in the literature [36,37] and although paradoxical effects were reported [18], a series of observations indicate that genetic traits in phase II enzymes, expected on mechanistic terms to increase risk, are indeed associated in humans with an increase in risk of cancer [19,38-43] or coronary heart disease [44,45].…”
Section: Discussionmentioning
confidence: 99%